Comparative analysis of the surgical treatment results in patients, suffering obliterating atherosclerosis of the lower extremities arteries with multi–level occlusion–stenotic affection on background of critical ischemia - А. М. Bytsai (Клінічна хірургія)
Objective. To improve the results of surgical treatment in patients, suffering obliterating atherosclerosis of the lower extremities (LE) arteries with a multi-level occlusive affection, occurring on background of critical ischemia (CІ).